Acridine-orange leucocyte cytospin (AOLC) test as an in-situ method for the diagnosis of central venous catheter (CVC)-related sepsis in adult risk patients - Baum, Heike von; Philippi, Pascale; Geiss, Heinrich K. (Zentralblatt für Bakteriologie, 1998)
The AOLC method for the in-situ diagnosis of catheter-associated septicemia was evaluated in adult intensive care patients. 55 blood samples and corresponding CVC tips were examined using the AOLC method, the semiquantitative roll plate method and the broth immersion method. In 4 patients (7.3%), a CVC-related septicemia was diagnosed, 10 patients (18.2%) showed a colonisation of their central venous access. The AOLC method was positive in 50% of the cases with CVC-related septicemia and in 20% of the colonized patients. Thus, we do not recommend the AOLC test as a routine method for the diagnosis of suspected CVC-related infection but as a facultative additional diagnostic measure for certain risk patients.